2004
DOI: 10.3748/wjg.v10.i19.2850
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection of submucosal tumor on posterior wall of gastric fundus

Abstract: AIM: Laparoscopic resection of tumors on the posterior wall of gastric fundus, especially when they are next to the esophagocardiac junction (ECJ), is both difficult and timeconsuming. Furthermore, it can lead to inadvertent esophagus stenosis and injury to the spleen. In order to overcome these difficulties, laparoscopically extraluminal resection of gastric fundus was designed to manage submucosal tumors located on the posterior wall of gastric fundus and next to ECJ. METHODS:From January 2001 to September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Moreover, various laparoscopic approaches for resection of gastric SMTs have been developed, depending on size, location, and transmural characteristics. 6,7,12,13 Despite these advances, no definite laparoscopic treatment guidelines have been established for gastric SMTs. A consensus meeting in 2005 concluded that laparoscopic surgery should be avoided, especially for GISTs larger than 2 cm, due to the risk of rupture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, various laparoscopic approaches for resection of gastric SMTs have been developed, depending on size, location, and transmural characteristics. 6,7,12,13 Despite these advances, no definite laparoscopic treatment guidelines have been established for gastric SMTs. A consensus meeting in 2005 concluded that laparoscopic surgery should be avoided, especially for GISTs larger than 2 cm, due to the risk of rupture.…”
Section: Resultsmentioning
confidence: 99%
“…5 Although there were some concerns about performing laparoscopic resections for gastric SMTs located near the pylorus or the esophagogastric junction, Song and colleagues 6 suggested that SMTs near the esophagogastric junction can be successfully resected by a tailored approach using LWR. Similarly, Ke and associates 7 reported that laparoscopic resection of a gastric fundus tumor on the posterior wall was safe and effective.…”
mentioning
confidence: 86%
“…It has also been reported that submucosal tumors in the gastric fundus or in the upper part of gastric body can be managed via laparoscopic proximal gastrectomy, whereas postoperative reflux esophagitis is common. For most benign gastric submucosal tumors, the range of such an operation is too large and the procedure is too invasive [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…2). Briefly, the laparoscope was positioned at portal A (laparoscopic portal, 10 mm); B and C were operating portals (10-12 mm), and an endoscopic gastrointestinal 1962-1968 1963 anastomosis (Endo GIA) stapler was inserted into the abdominal cavity through portal B; a five-finger grasping forceps was placed through portal D to retract the liver and expose the gastric tumors [2]. Tumor locations were first determined laparoscopically, for which three methods could be used: naked-eye inspection, instrument exploration, and intraoperative gastroscopy.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation